Research Progress on the Adsorption and Their Mechanisms of Heavy Metal in Soil By Microplastics - Ma, Jun; Zhang, Qinglei; Wang, Kai; Yang, Fan (International Journal of Agriculture and Food Sciences Research, 2025)
Microplastics (MPs), as emerging global contaminants, have garnered increasing attention due to their persistent nature, ubiquitous distribution, and recalcitrance to degradation. The co-occurrence of microplastics (MPs) and heavy metals (HMs) in soil systems has emerged as a critical global environmental concern, posing synergistic threats to ecosystem integrity and human health. Nevertheless, their interaction mechanisms remain poorly characterized. This review systematically examines the interplay between MPs and HMs in terrestrial environments, with emphasis on two key aspects: Interaction mechanisms between microplastics (MPs) and heavy metals (HMs) adsorption, influence factors on adsorption including polymer type, aging status, particle size/concentration of MPs, and physicochemical properties of HMs/soil matrices. Furthermore, coordinated multidisciplinary efforts are urgently required to establish risk assessment for MPs and HMs in soil systems and develop targeted remediation strategies.